Strategi Pembelajaran Pendidikan Moral pada Era Teknologi Informasi - Parji Parji (Universitas Negeri Malang, 2016)
In line with the recent rapid progress of the information technology, the strategy of teaching Moral Education in Indonesia should be consequently changed traditional, normative, and indoctrinative to more communicative, persuasive, and democratic way. This alternative strategy basically suggests four tips i.e. meaningfulness in application of knowledge, appreciation on learners, learning activity in real context, and taking focus on the process. This strategy enables learners to learn democratically which then results in their attitudes individual and social